Stress-Driven Evolution on Mismatched Ca2Co2O5 Oxide Material: From Geometry to the Electronic States - F. P. Zhang; Y. Sun; G. L. Zhang; X. Y. Shi; G. Q. Qin (Advances in Condensed Matter Physics)
The geometrical structures, phase stabilities, electron energy band structures, electron density of states, and atom recombination together with the electron conduction behaviors of the sandwiched Ca2Co2O5 with external stress of 1 GPa are intensively studied by the density functional theory method. The studying results show that the symmetry remains undisturbed; the strain to the stress response is anisotropic. The strain of microarchitecture induced by external stress is also anisotropic. There is stronger covalent binding between Co and O. The binding between Co and O within CdI2 like CoO2 is very much even covalent, and it is weakened under external stress. But the covalent Co-O binding within the rock salt like CaCoO layer is enhanced. The Ca-O binding strength is insensitive to external stress. An energy gap of 0.1 eV below Fermi level for the spin-up electron band disappears, and the two energy gaps are narrowed for the spin-down electron bands. The p orbital electrons form primarily the bands below Fermi level and the d orbital electrons form primarily the bands above Fermi level. The transitions from p orbital electrons to d orbital electrons produce the conduction. The CdI2 like CoO2 layer has been enhanced in terms of participating in the conduction properties with external stress of 1 GPa, and the capability of Co is enhanced while the capability of O is decreased.